Changes in physical activity indicators of Ukrainian students in the conditions of distance education - ANDRIEIEVA, OLENA; Hakman, Anna; Byshevets, Nataliia; Kashuba, Vitalii; Grygus, Igor (My University, 2023)
Purpose: purpose of the work is to determine the changes in physical activity indicators of Ukrainian students in the conditions of distance education caused by the quarantine restrictions and the conditions of the legal regime of martial law. Material & Methods: the study, which lasted from 2020 to 2023, involved 1528 higher education students from different regions of Ukraine. The International Physical Activity Questionnaire (IPAQ) was used to assess physical activity. The results were subjected to statistical analysis. Results: the results of the study of PA indicators in students showed that on average they had a normal PA score, which was 26.0 (22.0; 32.0) points for males, and 24.0 (19.0; 30.0) points for females. It was proved that, compared to female students, the PA score of male students was statistically significantly higher (U=226269.5; Z=7.329; p<0.05). The study of the dynamics of PA indicators demonstrated that while the PA score of higher education students, regardless of gender status, decreased from the beginning of quarantine restrictions (p<0.05), it did not differ statistically from the pre-quarantine level (p>0.05) in 2021. Nevertheless, with the outbreak of hostilities in the Ukraine, the PA score has decreased and continues to decline. There was an unprecedented increase in the percentage of students with low PA, which reached 43.1% and 60.1% among male and female students, respectively, in 2023. Conclusions: the analysis of the dynamics of PA in higher education students for the period from 2019 to 2023 revealed a decrease in the PA score during the distance learning period, regardless of gender status. The only exception was 2021, which can be explained by the adaptation of students to distance learning. Instead, the armed conflict in the country led to a sharp decline in the PA score and a statistically significant (p<0.05) increase in the proportion of students with low physical activity. Moreover, this trend continued in 2023. The findings of the study made possible to assess the extent of the negative impact of distance learning under quarantine restrictions and the legal regime of martial law on the PA in higher education students.
Keywords: higher education students, physical activity, distance education, female students, male students